EXPLORATION OF SERVICES ON CUSTOMER SATISFACTION IN THE SENSORIUM BALI RESTAURANT INDUSTRY - Evitarisma Yani, Ni Kadek; Kurnia M, Fakhruddin (Universitas Ichsan Sidenreng Rappang, 2024)
A restaurant is a place or building organized commercially, which provides good service to all its consumers in the form of food and drinks. Where customer satisfaction must be able to meet customer satisfaction. The level of customer satisfaction can be measured by comparing consumer expectations regarding the desired service quality with the reality received and felt. At this time, culinary development is seen very rapidly, because urban areas have many strategic areas for restaurants. This design plans a western food restaurant that focuses on Canggu regional culinary delights, strategically located near Batu Mejan Beach. The purpose of writing this research is to determine customer satisfaction at the Sensorium Bali Restaurant. I took 8 respondents who had been determined. The research method used is qualitative research, data collection techniques are carried out using interviews and observations. From the results of the research analysis, it can be concluded that customer satisfaction is determined by the quality of service shown in the aspects of Tangibles, Reliability, Responsiveness, Assumrance and Emphaty in restaurants.